Role of Corporate Social Responsibility in Sustainable Energy Development in Emerging Economy - Tiep, Le Thanh; Huan, Ngo Quang; Hong, Tran Thi Thuy (International Journal of Energy Economics and Policy, 2021)
This research aims to evaluate the impact of corporate social responsibility (CSR) on sustainable energy development (SED) by developing the role of mediating variables such as usage of renewable energy resources (URR) and sustainable energy supply (SES). We use qualitative and quantitative technique such as Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the data of collection from experts, economists, executives in Vietnam in 2020. The study has proved the corporate social responsibility (CSR) affecting directly to the sustainable energy development (SED). Besides, the findings suggest a positively significant impact of both sustaining energy supply (SES) and the usage of renewable energy resources (URR) on sustainable energy development (SED). Thus, the research brings the whole view of corporate social responsibility affects to the sustainable energy development (SED) through the URR and SES. This study contributed empirical work in the literature of corporate social responsibility, renewable energy, sustainable energy supply (SES) and sustainable energy development (SED). The outcomes of this study can be used by policy makers, economists, top management in the governmental office and even the corporate. A mediating role of SES as a value-added contribution to this study and can be consolidated and strengthened more in coming research. Keywords: Corporate Social Responsibility, Renewable Energy, Sustainable Energy Development, Renewable Energy Resources, Sustaining Energy Supply. JEL Classifications: M14, Q21, Q25, Q43, Q56 DOI: https://doi.org/10.32479/ijeep.10774